2015
DOI: 10.1016/j.enbuild.2015.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Heating performance of a solar chimney combined PCM: A numerical case study

Abstract: A c c e p t e d M a n u s c r i p t HIGHLIGHTS  The heating performance of the proposed system was numerically studied. Seven design and operating parameters of the proposed system were investigated. The first five parameters need to be carefully selected to maximize the performance. Thermal conductivity of absorber has less impact on the performance of the system.  Inlet air temperature is also an important factor in this study. ABSTRACTAn experimentally validated numerical model is developed to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The results showed that the inclusion of the PCM to a solar chimney reduces the air flow during charging period but increase it during discharging period compared with the solar chimney without PCM [37] However, PCM wallboards also present some disadvantages:…”
Section: Free Cooling and Heating Passive Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the inclusion of the PCM to a solar chimney reduces the air flow during charging period but increase it during discharging period compared with the solar chimney without PCM [37] However, PCM wallboards also present some disadvantages:…”
Section: Free Cooling and Heating Passive Methodsmentioning
confidence: 99%
“…Passive methods with TES integrated into several building components e.g. wallboards [27][28][29][30][31][32], glass [33], floor [34][35][36] or solar chimney [37] and active methods with the integration of TES in the celling [17][18][19][20], underfloor [21,22] and walls [16,38].…”
Section: Table 1 Pcm-tes Applicationsmentioning
confidence: 99%
“…PCMs are usually utilised in solar-PV applications as a passive temperature regulator [164][165][166][167]. PCMs can also be incorporated in solar chimneys replacing the conventional storage material and storing the solar energy gained from the absorber [168,169]. [170], and in (b) a solar chimney [168].…”
Section: Other Concepts Of Pcm Applications For Building Cooling and mentioning
confidence: 99%
“…PCMs can also be incorporated in solar chimneys replacing the conventional storage material and storing the solar energy gained from the absorber [168,169]. [170], and in (b) a solar chimney [168].…”
Section: Other Concepts Of Pcm Applications For Building Cooling and mentioning
confidence: 99%
“…In 2014, Liu and Li [181], [182] studied the thermal performance of a solar chimney which was integrated with the phase change material (PCM). They analyzed the PCM behaviors during its melting and solidification processes, absorber surface temperature, mass flow rate, and inlet and outlet air temperature difference.…”
Section: Analytical and Simulation Studiesmentioning
confidence: 99%